LINGUISTIC “CONSTRUCTION” OF THE GLOBALIZING WORLD: LINGUОSEMIOTIC ASPECT - T T Cherkashina; N S Novikova; T I Sayenko (Russian Language Studies, 2016)
The article offers a retrospective analysis of the interaction between the language and cogitative activity of the person in the globalization context. The paper addresses the issue of linguistic differences in cross-cultural communication and discusses communicative strategies that could be used to mitigate them. The authors argue that lingua-didactic multicultural education can help remove the main obstacle in the traditional teaching of Russian as a foreign language (RFL) - a “clash of cultures”; and not only can introduce a model of teaching to write, read, and speak in Russian, but can also offer a system of instruction that will allow the students to understand the way Russians think, which surely would make it easier for them to “translate” a text from one culture into another in a non-native “cultural environment” providing a polylingual format for interaction.